CameraIcon
CameraIcon
SearchIcon
MyQuestionIcon
MyQuestionIcon
Question

Prove, (43m-34n)2+2mn=169m2+916n2


Open in App
Solution

Given is 43m-34n2+2mn=169m2+916n2 ..(i)

Let us solve L.H.S separately.

Take L.H.S=43m-34n2+2mn

Using the Identity (a-b)2=a2+b2-2ab, we have

L.H.S=43m2+34n2-2×43m×34n+2mn

=169m2+916n2-2mn+2mn

=169m2+916n2 .......................................(ii)

From equation(i)and(ii), it is clear that L.H.S=R.H.S.

Hence, proved.


flag
Suggest Corrections
thumbs-up
14
BNAT
mid-banner-image